Assessment of tooth wear and its associated factors in adult patients visiting a dental hospital in Kathmandu, Nepal - Joshi, Rojin; Gautam, S; Joshi, B (Nepal Medical College Journal, 2020)
Tooth wear is a universal consequence of aging. It is an irreversible, multifactorial and destructive loss of dental hard tissues caused by either a mechanical or chemical process in the absence of caries or trauma. It can be a physiological and age dependent process. The risk factors that contribute to tooth wear are diet, bruxism, environment, occupation, oral health behaviour, acid regurgitation and use of tobacco. This study was done to find out if there is an association between tooth wear and its associated factors. So that we can educate the patients about the various factors causing tooth wear and minimise it. This cross sectional study was done amongst 339 patients. The clinical assessment of tooth wear was done using tooth wear index developed by Smith & Knight. A specifically designed questionnaire was used to seek information on risk factors of tooth wear. All patients were categorised into one of the following groups: Low Tooth Wear group, Moderate Tooth Wear group, Severe Tooth Wear group based on their individual tooth wear surface scores. Data were analyzed using Pearson’s chi-square test and descriptive statistics were calculated. We can see that the severity of tooth wear increases with age i.e, p≤0.05 which is statistically significant. Patients with self reported tooth sensitivity (60.5%) had a higher total tooth wear score than those who didn’t (39.5%) and the result was statistically significant. The results of our study show that tooth wear is a consequence of aging and there is an association between tooth wear and dentinal hypersensitivity.